(untitled) (CIPEEX, 2025)
Traditional strength training can cause post-exercise hypotension in both hypertensive and normotensive elderly individuals; however, few strength training methods have been studied in this population. The aim of this study was to evaluate whether a strength training session using the super-set method in hypertensive elderly individuals causes post-exercise hypotension (PEH). This is a randomized, controlled clinical trial with a cross-over design, with a sample of 30 hypertensive elderly individuals of both genders who performed two protocols: an experimental protocol (EP), which consisted of a strength training session using the super-set method, or a control protocol (CP), which did not involve exercise. The order in which the protocols began was randomized among the participants. Seventy-two hours after completing the initial protocol, the participants performed the remaining cross-protocol. Blood pressure (BP) was measured before (Pre), immediately after (T0), and for 60 minutes, every 15 minutes (T15, T30, T45, T60). As a result, it was observed that SBP of the EP increased in intragroup analysis immediately after, but without significance in the intergroup comparison. Return to baseline at T15, with a reduction in SBP at subsequent times, but with a statistical intergroup difference only at T45 and T60. Regarding DBP, there was no significant difference in the intragroup comparison in any protocol; however, in the intergroup analysis, at T60 (p=0.043), DBP was lower in PE. Thus, we observed that strength training using the superset method, performed by elderly hypertensive individuals, although it tends to increase SBP immediately after exercise, this increase was of small magnitude. There was rapid recovery of SBP at subsequent moments, with a significant reduction in SBP from 30 minutes post-exercise, with post-exercise hypotension then being observed.